2006
DOI: 10.1080/01449290600636512
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of handheld device use by older adults with age-related macular degeneration

Abstract: This study investigates factors affecting handheld human -computer interaction (HCI) for older adults with Age-related Macular Degeneration (AMD). This is largely an uncharted territory, as empirical investigations of HCI concerning users with visual dysfunction and/or older adults have focused primarily on desktop computers. For this study, participants with AMD and visually healthy controls used a handheld computer to search, select and manipulate familiar playing card icons under varied icon set sizes, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Established research into handheld device accessibility has demonstrated that users with visual impairment can effectively interact with small keypads and screens where non-visual input and output modalities are used to compensate for the lack of visual display resources 61 . With ongoing advances in mobile technologies, it is becoming ever more feasible for the visually impaired to rely on mobile handheld devices to capture information necessary for interrogating and understanding their surroundings and to access large amounts of information that can then be used to improve their level of independence, mobility, and quality of life.…”
Section: Mobile Device-based Assistive Technologymentioning
confidence: 99%
“…Established research into handheld device accessibility has demonstrated that users with visual impairment can effectively interact with small keypads and screens where non-visual input and output modalities are used to compensate for the lack of visual display resources 61 . With ongoing advances in mobile technologies, it is becoming ever more feasible for the visually impaired to rely on mobile handheld devices to capture information necessary for interrogating and understanding their surroundings and to access large amounts of information that can then be used to improve their level of independence, mobility, and quality of life.…”
Section: Mobile Device-based Assistive Technologymentioning
confidence: 99%
“…Kim and Albers (2002) conducted a user experiment to compare the difference in users' search behaviors for the same search task between desktop and mobile devices and concluded that the two types of search behaviors are basically the same; however, using a mobile device takes more time than a fixed device generally. Leonard et al (2006) studied the PDA usage behavior (including search, selection and other operations) of elderly users who are visually impaired and demonstrated that users with visual impairments can interact with the graphical user interface effectively if they specially designed the interaction system (including the 247 Locationbased mobile map search behavior interface designed and with the improvement and auditory feedback added). Compared with desktop devices, they found that the accuracy of the mobile search task is higher and that the cost is lower.…”
Section: Related Studiesmentioning
confidence: 99%
“…Some assistive technologies, which are developed to help disabled people, are well documented [6][7][8][9]. However, there are also some ethical issues that need to be considered while designing assistive technologies, which could benefit the disabled and elderly people [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%